2016
DOI: 10.1021/acs.analchem.6b03749
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Reactive Oxygen Species by a Carbon-Dot–Ascorbic Acid Hydrogel

Abstract: Detection of reactive oxygen species (ROS) is important in varied biological processes, disease diagnostics, and chemotherapeutic drug screening. We constructed a ROS sensor comprising an ascorbic-acid-based hydrogel encapsulating luminescent amphiphilic carbon-dots (C-dots). The sensing mechanism is based upon ROS-induced oxidation of the ascorbic acid units within the hydrogel scaffold; as a consequence, the hydrogel framework collapses resulting in aggregation of the C-dots and quenching of their luminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 68 publications
0
39
0
1
Order By: Relevance
“…In Figure 5C, Bhattacharya et al demonstrated an ascorbic acid gel encapsulating luminescent carbon dots for ROS detection. In the presence of ROS moieties, oxidation of the gel framework leads to aggregation of carbon dots and hence quenched luminescence [115].…”
Section: Metabolites and Reactive Speciesmentioning
confidence: 99%
“…In Figure 5C, Bhattacharya et al demonstrated an ascorbic acid gel encapsulating luminescent carbon dots for ROS detection. In the presence of ROS moieties, oxidation of the gel framework leads to aggregation of carbon dots and hence quenched luminescence [115].…”
Section: Metabolites and Reactive Speciesmentioning
confidence: 99%
“…光素(H 2 -DCF)的细胞内ROS检测的优异探针, 其氧 化产物钙黄绿素不会泄漏出细胞, 积累在线粒体中, 而二氢荧光素位于细胞质中, H 2 -Calcein的氧化可能 是电子直接转移到线粒体复合物I的结果 [110] . Jelinek 课题组 [111] [111] .…”
Section: 二氢钙黄绿素(H 2 -Calcein)是不同于二氯二氢荧unclassified
“…The fluorescent D‐π‐A compounds with ‐COOH group are important for NIR probes in the detection of living cell and in vivo imaging, flow cytometry, and reactive oxygen species sensors,, They are used in bio‐conjugation with affinity proteins and antibodies,, tagging quantum dots (QD) for resonance energy transfer, and carbon quantum dots for DNA sensing . Rhodanine‐3‐acetic acid (RAA) is a widely used acceptor in DSSCs ,.…”
Section: Introductionmentioning
confidence: 99%